STAGES OF DEVELOPMENT OF THE LEAN PRODUCTION CONCEPT AND SPECIAL FEATURES OF ITS ADAPTATION TO THE NATIONAL ECONOMY - Kolos, Iryna; Grechan, Alla (Journal of European Economy, 2017)
Features for territorial and chronological changes in the orientations of the concept of lean production argued. Strict adherence to internal standards that ensure quality and speed of execution of productive and administrative tasks with necessary expenses (without expenses) on creation of value for the consumer and economic benefits in the future is characteristic for Japan. In the US, the quality and performance is achieved by the Executive within a professional competence through the use of appropriate tools. For Europe, characteristic is the use of lean tools to produce the desired result in clearly planned terms. In France, especially important is compliance with social standards on labor conditions and environment protection while increasing productivity. Achievements of the world auto industry leaders in lean improvements that ensure adoption of lean thinking and lean culture are represented. The changes in the way of management of the enterprise are introduced by overcoming: (1) production issues (economic order quantity determination, establishing effective use of limited resources, development of efficient production schedule, planning of the production process and production areas); (2) organizational issues (value stream for all structural units determination, empowerment particular executor, focusing on the value stream for customer through process improvement and losses elimination). The feasibility of the introduction of company management on the principles of lean is proved taking into account peculiarities of the national economy through the prism of public-private partnership: public institutions, social organizations, top management of companies and stakeholders (primarily suppliers and customers). It was discovered that search for ways to overcome the external imbalances contributes to the development of partnerships at different levels: regional, national, supranational and global. The conclusion is made that the state support is crucial for the dissemination of the concept of lean production. Network of nongovernment organizations promotes ideas of lean thinking and practice through trainings, conferences and webinars (Internet-network), summits (full-time plenary). Top management must be ready for continuously transformations and trainings, development and improvement, which are the basis of successful practical implementation of the concept of lean production. This will increase productivity and improve working conditions through the mobilization of resources, increased standardization of processes and social dialogue with staff. Experience for the introduction of elements of the concept and implementation of the tools of lean production at domestic enterprises, which confirms the effectiveness and appropriateness of active implementation is considered.